Development and validation of a mathematical model to describe the growth of microencapsulated Lactobacillus acidophilus in a binary system composed of gellan gum (@limentech, Ciencia y Tecnología Alimentaria, 2016)
The objective of this work was to develop and validate a mathematical model that predicts the growth of microencapsulated Lactobacillus acidophilus in a binary gelling system composed of high and low acyl gellan gum. The growth rates of L. acidophilus were extracted from experimental data carried out by the Biotechnology, Food and Education research group (GIBAE) belonging to the University of Cartagena - Colombia. The extracted growth data were used to develop a model relating the growth rate of microencapsulated L. acidophilus. The Ratkowsky equation was used to model the data. Finally, the accuracy factors proposed by Baranyi et al., (1999) were used to analyze the development of the model. Experimental data for the growth of L. acidophilus showed a discrepancy with the predictions close to 7.2 % and a bias of 5.2 %. The developed model can be used to determine the effect of initial bacterial concentrations and temperature on optimization processes during the production of functional foods.
Keywords: Accuracy Factor; Bias Factor; Microencapsulation